Enzyme immunoassay for monitoring aflatoxins in eggs. (November 2015) - Anfossi, L.; Di Nardo, F.; Giovannoli, C.; Passini, C.; Baggiani, C.
Abstract: Rapid and sensitive competitive enzymatic immunoassays for measuring most relevant aflatoxins in eggs have been developed by synthesizing two hapten derivatives. Polyclonal antibodies raised against a hapten obtained from aflatoxin B1 (AFB1) were exploited to set an AFB1-selective assay, whereas antibodies obtained through immunising with a hapten derived from aflatoxin M1 (AFM1) allowed us to detect four principal aflatoxins (B1, G1, B2, and G2) and the most relevant AFB1 metabolite (AFM1) with detection limits in eggs of 0.3 μg kg −1 for AFB1, AFG1, and AFM1 and 3 μg kg −1 for AFB2 and AFG2, respectively. We also established a rapid and simple protocol for extracting aflatoxins from eggs by employing aqueous methanol (70%) followed by partitioning with hexane to remove fats. The whole analytical process is simple, very rapid (the extraction requires 14 min, and the assay is completed in 30 min) and proved to be accurate and precise enough (recoveries ranged from 84 to 100% and RSD% were within 20% for intra- and inter-assay experiments) to be proposed as a first level screening method for the monitoring of the occurrence of aflatoxins in egg. Highlights: Two rapid enzymatic immunoassays for measuring most relevant aflatoxins in eggs. An AFB1-selective assay and a group-selective assay were optimized. A rapid and simple protocol for extracting aflatoxins from eggs was established. The group-selective assay is accurate and precise. LOD in eggs is 0.3 μg kg −1 for AFB1, AFG1, AFM1 and 3 μg kg −1 for AFB2, AFG2.